2004
DOI: 10.1161/01.atv.0000128125.80559.9c
|View full text |Cite
|
Sign up to set email alerts
|

Factor XI–Dependent Reciprocal Thrombin Generation Consolidates Blood Coagulation when Tissue Factor Is Not Available

Abstract: Objective-Feedback activation of factor XI by thrombin is a likely alternative for tissue factor-dependent propagation of thrombus formation. However, the hypothesis that thrombin can initiate and propagate its formation in a factor XI-dependent and platelet-dependent manner has not been tested in a plasma milieu. Methods and Results-We investigated thrombin generation in recalcified platelet-rich plasma activated with varying amounts of thrombin or factor VIIa. Thrombin initiates and propagates dose-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…This concept is in accordance with the previous results [3,4,9] and can reinforce the 'fibrinolysis' hypothesis. In the absence of FXI, the moving thrombin peak is not formed and the local concentration of thrombin far from the activator at the time of clot formation is much lower [16].…”
Section: Editorialsupporting
confidence: 93%
See 1 more Smart Citation
“…This concept is in accordance with the previous results [3,4,9] and can reinforce the 'fibrinolysis' hypothesis. In the absence of FXI, the moving thrombin peak is not formed and the local concentration of thrombin far from the activator at the time of clot formation is much lower [16].…”
Section: Editorialsupporting
confidence: 93%
“…Thrombin formation is affected more significantly [2,3]. Still, both effects can be observed only in a limited range of experimental conditions: absence of FXI plays a role when there is low or zero TF concentration [2][3][4][5]. In these cases, FXI deficiency can lead to delayed clot formation and decreased thrombin generation.…”
Section: Editorialmentioning
confidence: 99%
“…36 To date, however, the platelet-derived cofactor for FXI activation by thrombin, and the underlying mechanism, has not been well defined. In this study, we showed that platelet releasates enhanced FXI activation by ␣-thrombin, an activity that was not (measured using a mechanical coagulometer).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have shown that FXI activation by thrombin is enhanced in the presence of activated platelets. [35][36][37] We recently showed that polyP of the size secreted by human platelets accelerates blood clotting reactions 20,21 and binds with high affinity to ␣-thrombin and FXIa. 24,31 Taken together, these findings led us to formulate and test the hypothesis that polyP, a natural polyanion secreted by activated platelets, 19,22 mediates FXI activation by ␣-thrombin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation